Informal approach based on user involvement to overcome uncertainties in a software project and to achieve high quality of an innovative product. (1st January 2013) - Begier, Barbara
There are serious problems with uncertainty referred to various aspects during evolutional development of an innovative software product. An open list of uncertain items in an expert system development is presented. In AI area some formal approaches to uncertainties are applied to build an expert system for medical diagnostics. Following the general idea applied in medicine, an informal approach to reduce uncertainties concerning product functions and handled data has been applied to improve software product quality. If symptoms of software 'disease' are learnt then the proper diagnosis and therapy may be specified. Various forms of user centeredness in a software process are discussed. Among other activities, the periodical assessment of a software product by its users is recommended to reduce some uncertainties. Users provide this way the regular feedback on a product. The experience, related to the developed non-trivial expert system assessed by its users, is described.